Desligamento automático de seção em semeadoras e taxa variada de sementes: novas abordagens para a semeadura precisa - Corassa, Geomar Mateus (2018)
Precision planting has been an emerging concept worldwide; however, the benefits of some technologies associated to this approach are still a knowledge gap. Studies evaluating the benefits of automatic section control technology for planters as well as a comprehensive analysis on soybean seeding rate prescription by yield environment, providing guidelines to variable rate seeding adoption were not yet assessed. Thus, the main goal of this study was to provide scientific knowledge about two new precision agriculture tools: a) automatic section control for planters and b) variable rate seeding for soybean. For the first study (a), the specific goals were to quantify the yield losses from double-planted areas in corn and soybean; quantity the planting area necessary to recover the investment from automatic section control technology; and measure the double-planted area proportion in Brazilian fields. For the second study (b), the main goal was to identify the optimum soybean seeding rate at varying yield environments, providing guidelines to variable rate seeding. Bayesian statistical inference models was used as the main approach. The main outcomes for the first study (a) were to: i) the use of automatic section control for planters increased profitability in both corn and soybean crops, by both seed savings and higher yields for corn and primarily by seed savings for soybean; ii) corn yield losses were primarily related to reduction in grain number per ear than the thousand grain weight component; iii) soybean yields were less sensitive to double-planted area due to a similar number of seeds per unit area and thousand seed weight; iv) when only corn was considered, economic return for the automatic section control was recovered with a smaller planted area; v) the average double-planted area proportion within fields was 5.5% of the total area; however, it increased linearly as planted area raised and for irregular field shapes. Finally, for the second study (b) we documented that i) seeding rate prescription can be optimized when yield environment is considered; the most probable optimum seeding rate should follow the trend from high to low yielding environment: low>medium>high; ii) seeding rate could be reduced by 18% at high relative to low environments, without penalizing yields; however, local factors and adjustments in seeding rates to achieve desired final stand densities with stand loss risks should also be considered.